Influence of Family Values on Sexual Behaviour: A Qualitative Study of the Perceptions of Pre-Service Student Teachers - Tshomo, Dechen; Tshomo, Ugyen; Dorji, Khandu; Gurung, Hari Maya; Sherab, Kezang (Advances in Social Sciences Research Journal, 2021)
Family values and culture play a crucial role in the sexual behaviour of young adults. Due to lack of research, it is difficult to understand how Bhutanese family values and culture impact the sexual behaviour of young adults. Bhutanese are known for taking pride in their family values and culture and this is vividly brought out in this paper as a context to the study being carried out. This study employed a qualitative approach to understand the perceptions of pre-service student teachers (16 Key Informant & 2 Focus Group Interviews) regarding the influence of family values on their sexual behaviour. The findings indicate a presence of strong influence of family values and culture on the sexual behaviour of young adults. However, the findings tentatively suggest that the age of parents, education of parents, region, and religion do not influence their sexual behaviour. This small-scale study sets a foundation for a more expansive study on the role of family values in shaping the sexual behaviour of college students. This paper also presents the implications of the findings.